Family acceptability of school‐based echocardiographic screening for rheumatic heart disease in a high‐risk population in New Zealand. (10th March 2015) - Perelini, Fiona; Blair, Nikki; Wilson, Nigel; Farrell, Alan; Aitken, Andrew
<x xml:space="preserve">Abstract</x> Aim Echocardiographic screening for rheumatic heart disease has been piloted in high‐risk areas in New Zealand and internationally, and fulfils most of the criteria for a targeted screening programme. The question of acceptability of rheumatic heart disease screening has not been assessed, and the aim of our study was to assess parental acceptability of a school‐based echocardiographic screening programme in a high‐risk population in New Zealand. Methods A post‐screening questionnaire was developed to survey parents of children who underwent echocardiographic screening. The families of 34 children with abnormal scan results and a sample of 80 children with normal scan results were surveyed by phone within 4 months of screening. Results Positive results were seen in all survey questions in both normal and abnormal scan groups. All families were supportive of an ongoing screening programme. Of children with abnormal results, 62% of their parents reported that they would treat their child differently; however, all responses were positive health‐promoting outcomes. Conclusion The study showed strong positive support for school‐based echocardiographic screening by a community with high acute rheumatic fever incidence. The study did not detect any short‐term negative effects in those with abnormal results. The survey result shows family and community support for the establishment of echocardiographic screening programmes in high acute rheumatic fever areas provided there is adequate infrastructural support.